Sankara Nethralaya Diabetic Retinopathy Epidemiology and Molecular Genetic Study (SN--DREAMS III): Study design and research methodology - Saumya Pal, Swakshyar (BioMed Central, 2011)
BACKGROUND: To describe the methodology of the Sankara Nethralaya Diabetic Retinopathy Epidemiology and Molecular Genetic Study III, an ongoing epidemiological study to estimate the prevalence of Diabetes and Diabetic Retinopathy in rural population of Kanchipuram and Thiravallur districts of Tamil Nadu, India and to elucidate the clinical, anthropometric, biochemical and genetic risk factors associated with diabetic retinopathy in this rural population. METHODS: Sankara Nethralaya Diabetic Retinopathy Epidemiology and Molecular Genetic Study III will be a mobile van based epidemiological study; 11,760 participants aged ≥ 40 years will be recruited from the study areas. Eligible subjects will undergo blood sugar estimation to diagnose Diabetes. Oral Glucose Tolerance Test will be done to conform diabetes. All subjects with diabetes will undergo complete information of knowledge, aptitude and practice of diabetes and diabetic retinopathy, Diet questionnaire, demographic data, socioeconomic status, physical activity, anthropometric measurements, and risk of sleep apnoea. A detailed medical and ocular history, a comprehensive eye examination including refraction, slit lamp biomicroscopy examination, indirect ophthalmoscopy, slit lamp biomicroscopy, digital stereo fundus photography and ultrasound of eye will be done in the mobile van. Blood will be collected for biochemical investigations including blood hemoglobin, glycosylated hemoglobin, lipid profile, urea and creatinine, genetic study. Urine will be collected for microalbuminuria. All fundus photographs will be graded at base hospital. Participants who need treatment will be sent to the base hospital. A computerized database is created for the records. CONCLUSION: The study is expected to provide an estimate of the prevalence of Diabetes and Diabetic Retinopathy and also a better understanding of the genetic, anthropometric and socio-economic risk factors associated with Diabetic Retinopathy in a Rural South Indian population.